Islamic Beliefs and Epistemic Defeaters: a Response to Baldwin and McNabb - Alsamaani, Nader A. (Sophia, 2022)
In this paper, I outline some exegetical and philosophical problems with Baldwin and McNabb’s epistemic defeater for Islamic beliefs. I maintain that their argument is based upon a misinterpretation of Quranic verses. I also argue that exceptional instances of divine deception inflicted upon the senses, if they indeed happen, should not undermine the general trust in our cognitive faculties. I conclude that virtually all Muslims are immune from Baldwin and McNabb’s proposed defeater and from the threat posed by divine deception in general.